Development of glioma prodrugs with site-specific activation by bioorthogonal palladium implants. (31st January 2018) - Adam, Catherine; Rubio-ruiz, Belén; Weiss, Jason T; Brennan, Paul; Unciti-broceta, Asier
Abstract: As the effectiveness of surgery is limited by the risk of injury to normal brain tissue, improving the prognosis for patients diagnosed with malignant glioma will require novel therapeutic approaches. Over many years this has focused attention on drug discovery strategies to identify efficacious new agents, but without success. Our innovative approach is to focus on improving drug tolerability, maximising dose delivery and reducing side effects. The invention of drug-releasing devices implanted in a tumour cavity after surgery provides an opportunity to overcome the limitation on clinical doses of cytotoxic drugs due to unwanted side‑effects. In the brain such a strategy delivers chemotherapy to the diseased area and circumvents the blood-brain barrier. However, to date such implants have suffered from problems such as limited carrying capacity and toxicity to the healing of surgical wound by the immediate release of chemotherapeutics after implantation at surgery. Our unique approach couples a prodrug with the use of a non-toxic and catalytic implant to trigger local release of cytotoxic agents. The prodrugs are rendered non-toxic by masking the functional-groups key to its mode of action, then unmasked by the palladium in the implant. This approach has potential to decrease side-effects, increasing the maximum therapeutic dose, and could improve the pharmacokinetic properties of the drug, potentially increasing penetration across the blood-brain barrier. Furthermore, as our palladium device catalytically unmasks the prodrug, the treatment course would not be limited by the lifetime of the implant and could be readily repeated in cases of recurrence. Our results in live cancer cells demonstrate that the cytotoxic activity of drugs can be switched off with our masking strategy and restored with the palladium implant, with no toxicity of the prodrug or implant alone. Ongoing in vivo experiments have also established that the palladium implant is biocompatible.